Islamic Leadership in Practice: A Review and an Educational to Common Existing Thought with Supply Chain Awareness System - Mahmud Tontowi; Yatim Riyanto; Soedjarwo Soedjarwo; Indriyati Adawiyah; Sugi Hartono (International Journal of Supply Chain Management, 2020)
Leadership in Islam for some scholars still struggling at the level of moral and spiritual content. The prime aim of this investigation is to investigate the impact of leadership practices with the mediating effect of supply chain management.  They have many views about leadership in Islam and the moral message that conveys. The commendable characters of the Prophet Muhammad PBUH an indicator of success. There has been little to discuss the leadership application process in Islam, the principle of leadership in Islam, and the process of congregational praying (Shalah al jama'ah). The data were gather from the praying leader by questionnaires and PLS-SEM was used for analysis. Praying in a congregation (jama'ah), there are several steps. First, the initial conditioning, which includes a place that meets the requirements, the sanctity of the body, clothing and place, the direction of the qibla. Second, selecting leaders is a very important process. How a leader is select and elected, also what are the category to own by the candidate. Third, the initial conditions of taking command over by the leader (imam). Many lessons can apply in everyday life, both for small organizational conditions and for a wider scale. Based on the search of the author, there is no concept of leadership in Islam that takes from the ongoing process of praying together (shalah al jamaah).